Critical infrastructure protection of ICT in Muslim world - Abdulrahman Ali, Sami Mohammed; Abdu, Muhammad; Ibrahim, Jamaludin (International Journal of Science and Research (IJSR), 2016)
This paper explain about many Muslim world get cyber cyberattack ,how vulnerable critical infrastructure protection especially in cyber in Muslim country such as Malaysia, Saudi Arabia, Turkey, and UAE compare to the west country , in this paper we know that most Muslim country are more vulnerable than west world because some reason. We recommend possible suggestions to reduce the effect of cyberattacks in Muslim countries